Assessment of breastfeeding practices among lactating mothers: a cross-sectional study - Goswami, Shweta; Khanna, Pardeep; Verma, Ramesh; Chayal, Vinod (International Journal Of Community Medicine And Public Health, 2018)
Background: Breastfeeding practice is known to play an important role in reducing child mortality and morbidity. The primary objective was to assess the breastfeeding practices in Rohtak and the secondary objective was to compare the breastfeeding practices in the rural and urban areas of Rohtak. Methods: This descriptive type of community based cross-sectional epidemiological study was conducted in rural and urban field practice areas attached to Department of Community Medicine, Pt. B. D. Sharma PGIMS, Rohtak. 500 Lactating mothers of 6-11 months old children were included in the study and data was collected using the pre-tested questionnaire on breastfeeding practices. Results: In our study, early breastfeeding rate was 32.2%, exclusive breastfeeding rate was 23.4%, bottle feeding rate was 35.4% and timely complementary feeding rate was 63.2%. Conclusions: Counselling sessions with the aim to promote breastfeeding are needed. Mothers as well as other family members should particularly be educated about the importance of early initiation of breastfeeding and to prolong exclusive breastfeeding.